Maresin1 ameliorates MSU crystal-induced inflammation by upregulating Prdx5 expression - Hui Jiang; DianZe Song; Xiaoqin Zhou; Feng Chen; Qingqing Yu; Long Ren; Qian Dai; Mei Zeng (BMC, 2023)
Abstract Background Maresin1 (MaR1) is a potent lipid mediator that exhibits significant anti-inflammatory activity in the context of several inflammatory diseases. A previous study reported that MaR1 could suppress MSU crystal-induced peritonitis in mice. To date, the molecular mechanism by which MaR1 inhibits MSU crystal-induced inflammation remains poorly understood. Methods Mousebone marrow-derived macrophages (BMDMs) were pretreated with MaR1 and then stimulated with FAs (palmitic, C16:0 and stearic, C18:0) plus MSU crystals (FAs + MSUc). In vivo, the effects of MaR1 treatment or Prdx5 deficiency on MSUc induced peritonitis and arthritis mouse models were evaluated. Results The current study indicated that MaR1 effectively suppressed MSUc induced inflammation in vitro and in vivo. MaR1 reversed the decrease in Prdx5 mRNA and protein levels induced by FAs + MSUc. Further assays demonstrated that MaR1 acceleratedPrdx5 expression by regulating the Keap1-Nrf2 signaling axis. Activation of AMPK by Prdx5 improved homeostasis of the TXNIP and TRX proteins and alleviated mitochondrial fragmentation. In addition, Prdx5 overexpression inhibited the expression of CPT1A, a key enzyme for fatty acid oxidation (FAO). Prdx5 protected against defects in FA + MSUc induced FAO and the urea cycle. Conclusion MaR1 treatment effectively attenuated MSUc induced inflammation by upregulating Prdx5 expression. Our study provides a new strategy by which Prdx5 may help prevent acute gout attacks.